2019
DOI: 10.1111/1556-4029.14126
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Behavior of Gunshot Residue: Recreational Shooter Vehicle Distribution

Abstract: The susceptibility for recreational shooters to transfer gunshot residue (GSR) to both the interior and exterior of a vehicle is investigated. A comprehensive sampling protocol was used to assess the most likely areas of GSR transfer from recreational shooter contact, such as the steering wheel and the area, the firearms were stored (the trunk). Up to 315 characteristic GSR, particles were found in several locations throughout the interior of a vehicle. As many as 876 characteristic particles were found throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The study of Gassner and Weyermann [41] showed that back seats were slightly more contaminated than the driver's seats and the number of compounds detected simultaneously was up to six out of the seven targeted. The study of Blakey et al [42] confirmed that vehicles frequently occupied by firearms users are a potential source for transfer of GSR to persons unrelated to firearm activity. Some studies also examined the background on certain target populations, such as police officers [47] and employees at firearms manufacturing facilities [48].…”
Section: Table 1 the Number Of Gsr Studies Listed By Year Of Publicat...mentioning
confidence: 93%
See 1 more Smart Citation
“…The study of Gassner and Weyermann [41] showed that back seats were slightly more contaminated than the driver's seats and the number of compounds detected simultaneously was up to six out of the seven targeted. The study of Blakey et al [42] confirmed that vehicles frequently occupied by firearms users are a potential source for transfer of GSR to persons unrelated to firearm activity. Some studies also examined the background on certain target populations, such as police officers [47] and employees at firearms manufacturing facilities [48].…”
Section: Table 1 the Number Of Gsr Studies Listed By Year Of Publicat...mentioning
confidence: 93%
“…Background studies are generally done to better understand the presence of GSR in very specific microenvironments. Background levels of GSR have been investigated in police vehicles [41] and recreational shooter vehicles [42], both being places of high risk of contamination [43][44][45][46]. The study of Gassner and Weyermann [41] showed that back seats were slightly more contaminated than the driver's seats and the number of compounds detected simultaneously was up to six out of the seven targeted.…”
Section: Table 1 the Number Of Gsr Studies Listed By Year Of Publicat...mentioning
confidence: 99%
“…The prevalence of IGSR in vehicles used by recreational shooters was investigated by Blakey et al, in order to evaluate the risk of secondary transfers associated with this type of activity [ 36 ]. Seven vehicles were investigated, with samples taken from 24 areas per vehicle.…”
Section: Inorganic Gsrmentioning
confidence: 99%
“…Research on the fate and behavior of GSR has refined the view that the presence of GSR on an individual's hands may, among several possibilities, be attributed to contact with a recently contaminated surface [2]. Key findings indicate that distinction between a shooter and secondary contamination/ bystander deposition must consider the contextual circumstances surrounding a case [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of GSR in the general environment is assumed to be rare and would generally be detected in the vicinity of a firearm discharge and/or surfaces with direct contact shortly after discharge. Any possibility of GSR contamination via secondary contact is expected to decline as a function of time since discharge [6,7].…”
mentioning
confidence: 99%